Dressing up as famous characters - Mumbai Archive Project Team (Jio Institute, 2024)
The parade provides an opportunity for participants to dress up as famous historical, mythological, and iconic figures from popular culture. This group is wearing masks and costumes from the Spanish crime drama television series Money Heist. The masks are based on the famous portrait of the Spanish painter Salvador Dalí.